Pindolol acts as beta-adrenoceptor agonist in orthostatic hypotension: therapeutic implications. - Man in 't Veld, A J (1981)
Three bedridden patients with severe orthostatic hypotension due to chronic autonomic failure were treated with pindolol (15 mg/day), a beta-adrenoceptor antagonist with partial agonist activity. While taking this drug the patients were free of orthostatic symptoms: they could walk, and standing blood pressure was maintained above 90/50 mm Hg. Supine heart rate rose during treatment by 12-21 beats/minute, and stroke volume and cardiac output by 12-24 ml and 1.5-3.1 l/min respectively. Supine blood pressure rose by 21-68 mm Hg systolic and 14-49 mm Hg diastolic. Pindolol 15 mg/day was therapeutically effective in these three patients with severe orthostatic hypotension due to chronic autonomic failure. Further studies in a larger series of patients are needed to confirm this result.